Perlindungan Hukum Terhadap Tenaga Kerja Wanita Terkait Hak Reproduksi Di Kota Manado - Korua, Jolanda M.; Mewengkang, Feiby S.; Tarore, Royke A.; Korah, Revy S.M.; Prayogo, Presly; Soepeno, Muhammad Hero (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2024)
This study aims to examine the protection of female workers related to reproductive rights. Women's reproductive rights are when they menstruate, become pregnant (pregnancy), give birth, and postpartum and certain conditions experienced by women. First, company regulations related to social security as women's rights in relation to reproductive rights. Second, how is the compensation given related to reproductive rights. Third, how is the company's guarantee for women related to the policies given by the company to workers related to reproductive rights. Based on the description above, this study was conducted using a normative legal research method that focuses on the application of legal protection for female workers related to reproductive rights. The research respondents were women who work in supermarkets, tourism, and entertainment sectors. This study focuses more on Legal Protection, especially social security for female workers related to reproductive rights in the city of Manado.